Renegotiating Social Citizenship - Democracy in Welfare Service States - Arne Wohlfarth (Social Work and Society, 2020)
Welfare states are subject to constant change. Societal and political changes in recent decades have made social services increasingly crucial in the provision of welfare. Such conversions in the welfare architecture are not remaining without implications for the citizens concerned.